ASSESSMENT OF KNOWLEDGE OF ANGANWADI WORKERS IN RURAL & URBAN AREA OF BHARUCH DISTRICT (International Journal of Food and Nutritional Sciences, 2023)
The government of India started the Integrated Child Development Services (ICDS) scheme in 1975. The Anganwadi is the important point for implementation of the ICDS scheme and the key role played in the implementation of this scheme is by the Anganwadi worker (AWW). Being a grass root functionary of ICDS programme, the AWW has to conduct different types of activities. 20 AWW from urban sector and 20 AWW rural sector selected for the sample of the study. Comparative study was done in urban and rural from rural area were assessed for their knowledge about the job activities. Researcher found that, greater number of the AWWS, in spite of having attended growth curves, earlier assessment of which experience of more than 20 years lacked proper knowledge and skill for interpretation.